THE EFFECTS OF VLOGGER CREDIBILITY AS MARKETING MEDIA ON BRAND AWARENESS TO CUSTOMER PURCHASE INTENTION - NUGRAHA, ANAS; SETYANTO, REFIUS PRADIPTA (INDONESIAN RESEARCH SOCIETY, 2018)
The purpose of this research is to know and analyze the effect of vlogger credibility as amarketing media on social media youtube on brand awareness to customer purchaseintention study on Traveloka with Arief Muhammad as a vlogger on youtube. The sample inthis study there are 150 respondents who are active on social media youtube. The researchmethodology used for this study is a case study with survey research method. Conveniencesampling technique derived from non- probability sampling techniques are used for sampleselection. Data were analyzed using Structural Equation Modeling (SEM) with SPSS andAMOS statistical software. The results of this study show that, (1) Credibility of vlogger hasa positive effect on brand awareness. (2) Attractiveness of vlogger has a positive effect onbrand awareness. (3) Expertise of vlogger has a positive effect brand awareness. (4) Brandawareness has a positive effect on consumer purchase intention.